1982
DOI: 10.3758/bf03332943
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in electrodermal response conditioning and self-report of discomfort: A phobia analogue

Abstract: The present study was designed as an analogue to the acquisition and extinction of a classically conditioned phobic response. Thirty electrodennally labile and 30 electrodennally stabile nonphobic male undergraduates were assigned randomly to one of two experimental conditions, utilizing either "prepared" or "unprepared" eSs, after Seligman (1971). It was hypothesized that electrodennally labile subjects, in contrast to stabiles, would require a greater number of trials to habituate to either es, would exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

1984
1984
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Given the failure to obtain a conditioning effect, there is, of course, no basis for expecting differential resistance to extinction of responses to fear-relevant stimuli such as reported by Öhman's group (see e.g., Öhman, 1979a). Similar problems are evident in another study using a differential conditioning procedure (McNally & Foa, 1986; see Öhman, 1993b, for a critique), whereas other alleged replication studies that have failed to produce a preparedness effect (e.g., Deitz, 1982; Emerson & Lucas, 1981; Maltzman & Boyd, 1984; McNally, 1981; McNally & Reis, 1982, 1984) have used dissimilar procedures (sometimes not even including an aversive UCS! ; e.g., Maltzman & Boyd, 1984) or primarily have addressed different issues (McNally & Reiss, 1982, 1984).…”
Section: Selectivity Of Input: Basic Findings On Selective Associatio...mentioning
confidence: 76%
“…Given the failure to obtain a conditioning effect, there is, of course, no basis for expecting differential resistance to extinction of responses to fear-relevant stimuli such as reported by Öhman's group (see e.g., Öhman, 1979a). Similar problems are evident in another study using a differential conditioning procedure (McNally & Foa, 1986; see Öhman, 1993b, for a critique), whereas other alleged replication studies that have failed to produce a preparedness effect (e.g., Deitz, 1982; Emerson & Lucas, 1981; Maltzman & Boyd, 1984; McNally, 1981; McNally & Reis, 1982, 1984) have used dissimilar procedures (sometimes not even including an aversive UCS! ; e.g., Maltzman & Boyd, 1984) or primarily have addressed different issues (McNally & Reiss, 1982, 1984).…”
Section: Selectivity Of Input: Basic Findings On Selective Associatio...mentioning
confidence: 76%
“…Verbal extinction to PP slides is possible in one trial using a reversal procedure similar to Wilson's (1968). Deitz (1982) demonstrated that conditioning of SCRs to the sight of a live snake does not differ significantly in rate of acquisition or resistance to extinction from conditioning to the sight of a comparable length of rope.…”
Section: Discussionmentioning
confidence: 94%
“…The results do not support the notion that differential responsivity to PP slides constitutes an experimental model of clinical phobias. McNally (1981) and Deitz (1982) provided further evidence indicating that conditioning SCRs to PP stimuli does not necessarily entail a qualitatively different kind of CS-UCS association than does conditioning to NP stimuli. McNally (1981) demonstrated that SCRs to phobic stimuli can be extinguished readily as a consequence of instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Compte tenu des nombreuses études menées par l'équipe d'Öhman et des résultats constants qu'ils obtiennent, les données actuelles peuvent paraî tre intrigantes. Cependant, d'autres chercheurs utilisant différents types de procédure de conditionnement (Deitz, 1982; Emerson & Lucas, 1981; McNally, 1981, 1986; McNally & Reiss, 1982; Vaitl et al 1985), de même que McNally et Foa (1986) avec un conditionnement différentiel sont incapables de montrer un effet d'apprentissage préparé.…”
Section: Discussionunclassified
“…Bien qu'on retrouve de faç on régulière dans leurs travaux, une plus forte résistance à l'extinction des réponses conditionnées avec des stimuli "préparés", on peut questionner le phénomène et critiquer la procédure. Tout d'abord, avec des procédures de conditionnement différentes, d'autres chercheurs n'observant pas un bel effet d'apprentissage "préparé" (Cook, 1981 & Hodes, 1981 cité par Cook, Hodes & Lang, 1986; Elen cité par Emmelkamp, 1982; & Hodes, 1981; Deitz, 1982; Emerson & Lucas, 1981; McNally, 1981, 1986; McNally & Foa, 1986; McNally & Reiss, 1982, 1984; Vaitl, Gruppe, & Kimmel, 1985). Ensuite, parmi les recherches recourant à la procédure de conditionnement différentiel d'Öhman, seules les expériences 5 et 6 de l'étude de Cook, Hodes, & Lang (1986) fournissent une confirmation modérée du modèle d'apprentissage "préparé" (Merkelbach, van der Molen & van den Hout, 1987).…”
unclassified